Kinerja Pengawas Madrasah Aliyah Swasta di Kota Bandung - Chadidjah, Sitti (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2019)
The result of superintendent performance at private madrasah aliyah in Bandung city is a legality document of madrasah. The documents include madrasah head documents, teacher documents, student documents and madrasah documents. Superintendent in performing their duties and functions to the madrasah are to monitor the completeness of madrasah administration. The purpose of this study is to find out more about the planning, implementation, performance results, supporting factors and performance inhibitors. This study is a narrative qualitative, with nine participantst that consist of four participants from the superintendent, four participants from the heads of the madrasah, and one participant from the section head of the madrasah. Data were collected through interviews, documentation studies, and observations. Then the data is analyzed by triangulation method.The results of the interviews, observation and documentation study are found that not all madrasah superintendent perform performance planning at the beginning of the academic year. The implementation of superintendent performance is monitoring and nurturing the head of madrasah and teachers through document. The results of the superintendent performance in the madrasah are documents from the completeness of the documents it will be the release of certification money for teachers and head of madrasah, and the liquidity of government aid funds. The inhibiting factor of superintendent performance is the lack of competence of the madrasah head, so the response to the change seems to be slowly accepted. Performance support factors are supervisory work means which are adequate. The control of superintendent performance is still less than the maximum. The lack of working hours and supervision of superintendent performance results need to be more reviewed. superintendent on the superintendent performance has not been a genuine concern from related parties.